Book of Abstracts of the 1st International PhD Conference of Doctoral School of University of Maribor: Green Transition: Advancing Academia’s Role in SustainableInnovation (University of Maribor Press, 2024)
With this publication, we aim to inform doctoral students, university professors, and the interested public about current topics being researched by doctoral students in the field of the green transition and the role of the academic environment in developing sustainable solutions. The summaries of the publications provide insight into the research problems doctoral students are addressing in this area and the solutions they propose.